Implementasi Strategi Marketing Mix Syariah pada Produk Obu Jamu di CV. Dua Laba Batam dan Manfaatnya - Choiruddin Choiruddin; IGN Oka Widana; Amie Amelia; Pitri Yandri (Syntax Corporation Indonesia, 2024)
This study aims to investigate the implementation of the sharia marketing mix strategy on CV. Two Profits in Batam City for OBU Jamu products and their benefits for the surrounding community. Using a qualitative approach and case studies, this study involves an in-depth analysis of the sharia marketing strategy implemented by CV. Two Profits, including in the aspects of product, price, distribution, and promotion. The basic concept of sharia marketing and the characteristics of OBU Jamu products are also the focus of this research. Through interviews, observations, and document analysis, this study found that CV. Dua Laba has successfully implemented a sharia marketing strategy on their OBU Jamu products well. Packaging that is in accordance with sharia principles, fair and transparent pricing, distribution through channels that are in accordance with sharia principles, and promotions that prioritize sharia values are integral parts of their marketing strategy. The impact of this implementation is also felt by the surrounding community, including increased awareness of sharia products, local economic empowerment, and positive social and cultural impacts. The results of this study contribute to the understanding of sharia marketing in the context of the herbal medicine industry in Indonesia, as well as provide insights for other companies that want to implement sharia marketing strategies. Practical recommendations are also recommended for CVs. Dua Laba and other stakeholders in optimizing the implementation of sharia marketing strategies on their OBU Jamu products.